+0  
 
0
345
2
avatar

how to simplify tan squared X- sin squared X to tan squared X times sin squared X

Guest May 30, 2017
 #1
avatar+92856 
+2

 

I guess we have

 

[ tan^2x  -  sin^2x ] / [ tan^2x * sin^2x ]  =

 

[ sin^2x / cos^2x   -  sin^2x] / [ sin^2x * sin^2x / cos^2x ] =

 

[sin^2x  ( 1/cos^2x  - 1 ) ] / [  sin ^2x * (sin^2x / cos^2x ) ]  =

 

[ sec^2 x  - 1 ]  / [ sin^2x / cos^2x ]  =

 

tan^2x  / tan^2x   =  

 

 

 

cool cool cool

CPhill  May 30, 2017
 #2
avatar+7340 
+1

how to simplify     tan2 x - sin2x     to     tan2x * sin2x

 

tan2 x - sin2x

= sin2x / cos2x    -  sin2x cos2x / cos2x

= [ sin2x - sin2x cos2x ] / cos2x

= [ sin2x ( 1 - cos2x ) ] / cos2x

= [ sin2x (sin2x) ] / cos2x

= sin2x / cos2x * sin2x

= tan2x * sin2x

hectictar  May 31, 2017

1 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.